The role of creativity and innovation in diversifying seaweed products (Gliseria sp) to improve the welfare of MSMEs: Peran kreativitas dan inovasi dalam diversifikasi produk rumput laut (Gliseria sp) untuk meningkatkan kesejahteraan UMKM - Sriyono; Nihlatul Kudus (Academia Open, 2023)
This study aims to provide an important overview of the role of creativity and innovation for MSMEs to diversify products that are useful for improving the welfare of MSMEs. The data taken is primary data through detailed interviews / in-depth interviews on ten informants who are considered important and can provide answers in accordance with the questions carried out by researchers including MSME actors, local governments and experts in the field. Test the validity of data using Credibility Test and Transferability Test. The result found in this study is that MSMEs do not have adequate creativity and innovation in improving welfare. The conclusion of this study is that MSMEs do not yet have creativity and innovation towards diversification. So that MSMEs are unable to improve their welfare. Highlights: Lack of Creativity and Innovation: The study highlights the insufficient level of creativity and innovation within MSMEs, indicating a crucial barrier to diversification and improved welfare. Primary Data from Informants: Utilizing primary data from in-depth interviews with key informants, including MSME actors, local governments, and field experts, ensures a comprehensive understanding of the challenges and opportunities. Credibility and Transferability Tests: Employing credibility and transferability tests enhances the reliability of the data, strengthening the validity of the study's findings about the limited creativity and innovation hindering MSMEs' welfare enhancement. Keywords: Creativity, Innovation, MSMEs, Welfare, Diversification